To determine the solution of the equations \( -3x - y = 3 \) and \( y = -3x + 4 \), we first need to rewrite the given equation into a more recognizable form.
The first equation, \( -3x - y = 3 \), can be rearranged to find \( y \):
\[ -y = 3 + 3x \] \[ y = -3x - 3 \]
Now we have two equations to analyze:
- \( y = -3x - 3 \) (Equation 1)
- \( y = -3x + 4 \) (Equation 2)
Next, we note the slopes of both lines:
- The slope of Equation 1 is -3.
- The slope of Equation 2 is also -3.
Since both lines have the same slope, they are parallel. Additionally, because they have different y-intercepts (one is -3 and the other is 4), they will never intersect.
Based on this information, the correct answer is:
Two parallel lines are graphed across a coordinate plane. One line is dotted while the other is solid.